Peningkatan Kualitas Hidup Bersih Dan Sehat Masyarakat Kelurahan Lewirato Melalui Pembuatan Tempat Sampah Dan Papan Edukasi Kebersihan - Mulyadin Mulyadin; Ismunandar Ismunandar; Nurlayli Istiqomah; Muhammad Rizki Bima Putra (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Lewirato District aims to improve cleanliness and health by fostering a caring attitude among its residents. The strategy includes educational programs, community clean-up drives, and sustainable practices. Regular monitoring and evaluation ensures program effectiveness and provides benefits to the community. The KKN program was implemented in Mpunda District, Bima City, West Nusa Tenggara, from August 2023 to September 2023, aiming to improve the quality of life of residents in Lewirato Village. This initiative includes planning, implementation, and evaluation stages, with a focus on waste management, environmental cleanup, and community involvement. Program achievements are assessed throughout the process. This community service activity for STIE Bima in Lewirato Village produces output in the form of a unified organic and inorganic waste bin, a clean landfill environment, a clean and comfortable field, water and the environment. the surrounding environment is not polluted and clean, and a clean environment is pleasing to the eye. With this activity, it is hoped that the people of Lewirato can develop a more caring attitude and develop themselves in an effort to maintain a clean and healthy environment. community environment. Increasing the clean and healthy quality of life for the people of Lewirato will have an influence on other sub-district communities.